ChemInform Abstract: 2‐(1‐Hydroxypropyn‐2‐yl)‐1‐vinylpyrroles: The First Successful Favorsky Ethynylation of Pyrrolecarbaldehydes. Issue 22 (15th May 2015) - Ivanov, A. V.; Shcherbakova, V. S.; Ushakov, I. A.; Sobenina, L. N.; Petrova, O. V.; Mikhaleva, A. I.; Trofimov, B. A.
Abstract: The reaction is achieved by the super basic catalytic composition NaOH/EtOH/DMSO.